Pattern of psychoactive substance use by students - Ribeirão Preto - Margarita Antonia Villar Luis; Sandra Cristina Pillon; Moacyr Lobo da Costa Junior; Paulo Sérgio Ferreira; Jaqueline Queiroz de Macedo
The aim was to analyze the use of psychoactive substances among students in their final year of middle school and high school in Ribeirão Preto and reflect on the pattern of psychoactive drug use based on epidemiological studies conducted over the last century. This is a cross-sectional study using a self-administered questionnaire in 29 municipal schools in Ribeirão Preto - SP with 3,955 students. We realized the need to implement specific public policies, provide alternative spaces for leisure, train teachers to motivate students to remain at school, and provide programs and activities that meet their social reality and that are applicable.